PERAN GURU PENDIDIKAN AGAMA KRISTEN MENGATASI MASALAH ANAK BROKEN HOME (Studi Kasus di SMP Immanuel Batu) - Sriulina, Jennyta (STIPAK Malang, 2024)
The aim of the research is to find out the characteristics of children who are victims of broken homes at Immanuel Batu Middle School, to know the role of Christian Religious Education Teachers in helping children who experience recurring homes at Immanuel Batu Middle School, and to find out the impact of Christian Religious Education in helping children who experience recurring homes at Immanuel Batu Middle School. The research method is an instrumental case, namely a case that is studied to explain the process of generalization, in other words the case is positioned as a means (instrument) to show explanation and understanding of something other than what is usually explained and the results will be used to perfect the concept or theory that has been existing or creating a new theory. The research results concluded that (1) learning methods that involve exemplary values, direct guidance and opportunities to practice religious values to encourage behavior in accordance with basic values are in accordance with the characteristics of students who experience problems in the family, (2) a moral school climate will reduce unhealthy competition and not tolerate behavior that hurts oneself and others, (3) the community's contribution to the development of children's religious morals is very important because a healthy environment will be an arena that can equip children with their identity as normal human beings and the ownership of freedom. unconditional, (4) schools must support or motivate students to have a commitment to implementing learning models that refer to an exemplary approach of caring for others and, (5) a friendly school climate will reduce psychological pressure, especially for children who are victims of broken homes without eliminating school rules and regulations.